Choose to learn : teaching for success every day - Osguthorpe, Russell T.; Osguthorpe, Lolly S. (Thousand Oaks, CA : Corwin Press, 2009)
Discover how the application of eight powerful principles can motivate students, increase every learner's self-confidence, and encourage individuals to go beyond familiar goals to take manageable risks.
Includes bibliographical references
Keywords: Learning; Motivation in education; Teachers -- Attitudes; Academic achievement; Success